2012
DOI: 10.5433/1679-0359.2012v33n4p1251
|View full text |Cite
|
Sign up to set email alerts
|

Atividade enzimática do solo sob sistema de produção orgânica e convencional na cultura da cana-de-açúcar em Goiás

Abstract: ResumoObjetivou-se avaliar a atividade das enzimas ligadas ao ciclo do carbono, à mineralização do fósforo e atividade enzimática total do solo cultivado com cana-de-açúcar orgânica certificada com e sem revolvimento do solo, orgânica em certificação, convencional com e sem queima da palhada e uma área remanescente de Cerrado no município de Goiatuba, GO, Brasil. Foi realizada coleta de solo em março (período chuvoso) e setembro (período de estiagem) de 2009, na profundidade de 0-10 cm, para análises de matéri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
5
1
3
Order By: Relevance
“…Unlike the results of the present study, other studies carried out in Brazilian tropical soils, in savannas (Cerrado) (EVANGELISTA et al, 2012) and tropical forest (Mata Atlântica) (SANT 'ANNA et al, 2009) The use of enzyme activities (including FDA hydrolysis) as indicators of soil quality can be quite troublesome, since in many cases it is difficult to elucidate possible changes in enzyme activity in response to a given factor, or even establish relations of cause and effect between the occurrence of a disturbing event and changes in soil enzyme activity (GIANFREDA et al, 2005). However, fluorescein diacetate hydrolysis is said to be a sensitive method to estimate microbial activity in hydromorphic soil (Planosol) of subtropical lowlands in southern Brazil, constituting a bioindicator of soil quality in areas subjected to different types of agricultural management under those conditions (MATTOS et al, 2009).…”
Section: Resultscontrasting
confidence: 97%
“…Unlike the results of the present study, other studies carried out in Brazilian tropical soils, in savannas (Cerrado) (EVANGELISTA et al, 2012) and tropical forest (Mata Atlântica) (SANT 'ANNA et al, 2009) The use of enzyme activities (including FDA hydrolysis) as indicators of soil quality can be quite troublesome, since in many cases it is difficult to elucidate possible changes in enzyme activity in response to a given factor, or even establish relations of cause and effect between the occurrence of a disturbing event and changes in soil enzyme activity (GIANFREDA et al, 2005). However, fluorescein diacetate hydrolysis is said to be a sensitive method to estimate microbial activity in hydromorphic soil (Planosol) of subtropical lowlands in southern Brazil, constituting a bioindicator of soil quality in areas subjected to different types of agricultural management under those conditions (MATTOS et al, 2009).…”
Section: Resultscontrasting
confidence: 97%
“…The authors claim that FDA activity represents the heterotrophic potential of Rev Bras Cienc Solo 2017;41:e0160239 soils because it represents the activity of enzyme groups that decompose organic matter (Dick et al, 1996). Other studies (Evangelista et al, 2012;Silva et al, 2012) have shown that the activity of several enzymes is influenced by the levels of organic matter in soils.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial respiration and the hydrolysis of fluorescein diacetate (FDA) are some of the parameters most commonly used to evaluate microbial activity in soils; they define the total enzymatic activity in a soil where microorganisms are the main source of enzymes (Pereira et al, 2004;Green et al, 2006;Batista et al, 2008;Carvalho et al, 2008;Carneiro et al, 2009;Evangelista et al, 2012). Research has shown that these factors are significantly influenced by soil use and management methods (Pell et al, 1998;Stenström et al, 1998;Arshad and Martin, 2002;Schloter et al, 2003;Gil-Sotres et al, 2005;Batista et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of ecosystem productivity, both in plantations and forests, greatly depends on the process of organic matter transformation and consequently on the microbial biomass (Gama-Rodrigues & Gama-Rodrigues, 2008). Microorganisms constitute the main source of soil enzymes, and the evaluation of enzyme activity has been reported as an effective indicator of soil quality, organic matter decomposition and nutrient availability resulting from management practices (Evangelista et al, 2012).…”
Section: Introduction and Objectivesmentioning
confidence: 99%